PENGARUH INTELLECTUAL CAPITAL TERHADAP PROFITABILITAS PADA PERUSAHAAN FARMASI DI BEI - SHEARLY PUTRI WIJAYA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Intellectual capital is the knowledge that can assist companies in creating a product that attracted the attention of consumers. The existence of intellectual capital, companies can maximize existing resources to create innovative products. Therefore, this study aims to examine the effect of intellectual capital on the profitability of the pharmaceutical company listed on the Indonesia Stock Exchange 2006-2010 period.Quantitative research design is a hypothesis. Research variables used are intellectual capital (VAIC) and profitability, including return on asset (ROA), return on equity (ROE) and earnings per share (EPS). Companies studied were pharmaceutical company listed on the Indonesia Stock Exchange study period from 2006-2010. Type of data used is quantitative data obtained from the IDX website and ICMD. Data analysis techniques using simple linear regression.The result showed that the positive effect on intellectual capital return on asset (ROA), return on equity (ROE) and earnings per share (EPS). This is because the company utilize and manage the intellectual capital owned by the well and the maximum, so it can provide added value to earnings per share.